Revised classification of glaciofluvial landforms in the Finnish sector of the Fennoscandian Ice Sheet - Hovikoski, Jussi; Palmu, Jukka-Pekka; Väänänen, Tapio; Valkama, Markus; Ojala, Antti E. K.; Putkinen, Satu; Pitkäranta, Reijo (Wiley, 2026)
Effective and sustainable land use, conservation, and the use of geological resources (incl. raw materials, aggregates and groundwater) require a clear classification system of sedimentary units, with well-defined vocabulary and unified mapping practices. To ensure harmonization of the GTK's (Geological Survey of Finland) map database of Finnish Quaternary surficial features, classification criteria for glaciofluvial landforms have been updated. The work is based on earlier geological field mapping of surficial Quaternary deposits as well as previous and ongoing LiDAR DEM-based mapping of glaciofluvial landforms in Finland. In this paper, we present the updated classification and terminology, discuss the defining criteria of glaciofluvial map unit types and show their representative examples. Inherent challenges and limitations of this remote sensing-based mapping approach are also discussed.